2018
DOI: 10.1007/s10549-018-4669-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital image analysis of Ki67 proliferation index in breast cancer using virtual dual staining on whole tissue sections: clinical validation and inter-platform agreement

Abstract: PurposeThe Ki67 proliferation index is a prognostic and predictive marker in breast cancer. Manual scoring is prone to inter- and intra-observer variability. The aims of this study were to clinically validate digital image analysis (DIA) of Ki67 using virtual dual staining (VDS) on whole tissue sections and to assess inter-platform agreement between two independent DIA platforms.MethodsSerial whole tissue sections of 154 consecutive invasive breast carcinomas were stained for Ki67 and cytokeratin 8/18 with imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 22 publications
5
77
0
1
Order By: Relevance
“…NordiQC), involving comparison of laboratory scores with reference scores in periodic assessment challenges, will probably improve interobserver reproducibility further. Recent studies suggest that an even higher level of concordance can be achieved with automated image analysis . The IKWG is actively conducting studies in this area to assess how artificial intelligence may help to standardise Ki67 assessment .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NordiQC), involving comparison of laboratory scores with reference scores in periodic assessment challenges, will probably improve interobserver reproducibility further. Recent studies suggest that an even higher level of concordance can be achieved with automated image analysis . The IKWG is actively conducting studies in this area to assess how artificial intelligence may help to standardise Ki67 assessment .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that an even higher level of concordance can be achieved with automated image analysis. [35][36][37][38] The IKWG is actively conducting studies in this area to assess how artificial intelligence may help to standardise Ki67 assessment. 35,38 Also, concordance between Ki67 scores on core biopsies and excision specimens is currently being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The data were presented as fitted regression lines with 95% confidence forecast bands and coefficient of determination ( R ‐squared). Inter‐platform agreement between the different methods of manual counting and image analysis was further assessed using Bland–Altman plots . The data were calculated using the difference between the results from Positive Cells‐Manual (combined [counters 1–3] or individually [counters 1–4]) and Positive Cells‐CellProfiler or DAB‐regions‐CellProfiler against the mean of the two measurements .…”
Section: Methodsmentioning
confidence: 99%
“…At the recent 2017 St. Gallen International Expert Consensus Conference, an issue of caution was raised concerning the reproducibility of IHC for Ki‐67 and the implications of this variability for clinical decisions [50]. Multiple groups have previously demonstrated that inter‐observer variability can be negated by scoring Ki‐67 in a reproducible and quantitative manner using digital analysis; for instance, using the Definiens Tissue Studio software (Definiens, Munich, Germany) and the Aperio ePathology image analysis system (Leica Biosystems, Wetzlar, Germany) [51‐54]. This mIHC/IF digital analysis can also be performed using the PerkinElmer Vectra platform (PerkinElmer, Inc., Waltham, MA, USA) followed by inForm software (PerkinElmer, Inc., Waltham, MA, USA) [55‐57], which circumvents this limitation as well.…”
Section: The Limitations Of Ihcmentioning
confidence: 99%